STUDY OF TECHNOLOGICAL CHAINS FOR RAPID PROTOTYPING OF ORTHODONTIC DENTAL PRODUCTS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The paper presents results from studying the possibilities of digital layering technologies (DLP SLA - Digital Light Projector Stereolithography) for construction of biomedical orthodontics devices (aligners). Experimental data on the mechanical and aesthetical properties (transparency) of the materials used has been studied in comparison with the conventional technologies for producing the aligners - Vacuum Forming (VF). The paper discuss the influence of the design of the devices (e.g. thickness) and technological parameters (e.g. stirring time) of the processes on the mechanical properties and orthodontics functionality of the materials as well as the quality and accuracy of the devices (models and functional prototypes for dental applications).